Does US foreign aid undermine human rights?: the "thaksinification" of the war on terror discourses and the human rights crisis in Thailand, 2001 to 2006 - Regilme, Salvador Santino F., Jr. (Human rights review, 2018)
What is the relationship between Thailand’s human rights crisis during Prime Minister Thaksin Shinawatra’s leadership (2001–2006) and the USA-led post-9/11 war on terror? Why did the human rights situation dramatically deteriorate after the Thaksin regime publicly supported the Bush administration’s war on terror and consequently received US counterterror assistance? This article offers two conceptual arguments that jointly demonstrate a constitutive theoretical explanation, which shows that counterterror and militaristic transnational and national discursive structures enabled the strategy of state repression in Thailand under Thaksin. The first concept refers to strategic localization, which refers to how the Bush administration’s global war on terror—and its consequent overarching emphasis on military security—provided an opportunity for the Thaksin administration to strategically localize the global threat of terrorism in ways that could seem relevant to the local Thai context. The second concept pertains to resource mobilization, which shows how converging US and Thai discourses on military security facilitated Thaksin’s strategy of increased state repression that led to the proliferation of state-led human rights abuses. This research article contributes to the human rights literature in two ways: (1) by highlighting how foreign aid programs and its constitutive political discourses shape recipient countries’ domestic human rights situation (2) and by tracing the macro-political factors that lead to the eventual democratic decay of contemporary Thailand.